Pengaruh Persentase Puree Labu Kuning dan Substitusi Tepung Sorgum Terhadap Sifat Fisik, Kimia, dan Tingkat Kesukaan Dodol Garut - Pasa Ramada Permana, Harpa; Slamet, Agus; Perwita Sari, Yuli (Universitas Mercu Buana Yogyakarta, 2026)
This study examines the innovation of dodol garut as a traditional Indonesian food, by increasing its nutritional value through the addition of pumpkin puree and the substitution of rice flour with sorghum flour. Pumpkin is a source of high levels of natural antioxidants, while sorghum provides dietary fiber and vegetable protein. The purpose of this study is to produce dodol garut with a preferred substitution ratio of pumpkin puree and rice flour for sorghum flour, as preferred by panelists. The study applied a completely randomized design (CRD) with two treatment factors, namely the ratio of pumpkin puree (23%, 28%, 33%) and rice flour substitution: sorghum flour (60:20g, 40:40g, 20:60g). On selected samples, three replicates were conducted with 2 batches. Physical testing included color and texture. Chemical analysis included moisture content, ash, protein, fat, carbohydrates, β-carotene, and antioxidant activity. The preference test consisted of the parameters of color, aroma, taste, texture, and overall. The data were statistically analyzed using IBM SPSS Statistics 25, starting with univariate tests, followed by one-way ANOVA and Duncan’s Multiple Range Test (DMRT) for significant differences. The results showed that the combination of pumpkin puree percentage and sorghum flour substitution significantly affected the color and texture. The most preferred dodol garut by the panelists was the percentage of pumpkin puree 33% and the substitution of rice flour: sorghum flour 40:40g. The chemical composition of dodol garut at the percentage of pumpkin puree 33% and the substitution of rice flour: sorghum flour 40:40g had a β-carotene content of 34.91 µg/g and antioxidant activity of 13.21%. The proximate composition was 11.80% water content, 0.84% ​​ash content, 10.51% protein content, 7.60% fat content, and 65.42% carbohydrate content.